Generation and Thermal Properties of a Dual-Transverse-Mode With Dual-Polarization and Dual-Frequency by a Dual-Medium Microchip Laser - Zilong Zhang; Kun Gui; Changming Zhao; Haiyang Zhang; Yuxiao Xing (IEEE Photonics Journal)
A dual-polarization, dual-frequency and dual-transvers-mode laser beam is generated by a dual-medium microchip laser. The dual-transvers-mode includes a linearly polarized LG01 mode and a perpendicular polarized TEM00 mode, which have different optical frequencies. How is the beat frequency of the dual-mode influenced by the thermal factors, including cooling temperature of birefringent crystal and thermal effect of gain medium, is experimentally investigated and theoretically analyzed. These studies offer an extension and better understanding of the dual-medium based dual-frequency laser, which is of important applications in coherent Lidar detection and optical communications.